The impact of the timing of pasta intake on sleep quality and health outcomes: a protocol for a randomized controlled trial - S. Lotti; M. Dinu; A. Napoletano; G. Pagliai; M. Tristan Asensi; I. Giangrandi; F. Cesari; M. Becatti; A. Amedei; C. Fiorillo; R. Marcucci; B. Colombini; et al. (Trials)
Abstract Background Pasta is a fundamental component of the Mediterranean diet and a key source of carbohydrates. Despite its nutritional benefits, misconceptions persist regarding its potential to promote weight gain, particularly when consumed at dinner. While no evidence supports this concern, emerging chrononutritional research suggests that evening carbohydrate intake may positively influence sleep quality by promoting serotonin production. This study aims to assess, for the first time, whether pasta consumption (lunch vs. dinner) affects sleep quality, circadian rhythms, cardiometabolic health, and gut microbiota composition in healthy, normal-weight adults. Methods A 7-month randomized, open-label, cross-over trial will enroll 70 participants, assigned to two isocaloric, Mediterranean-style diets differing only in pasta consumption timing. Each phase will last 3 months, separated by a 1-month wash-out period. At the beginning and end of each phase, participants will wear an actigraph for 7 days and provide saliva, blood, and stool samples. Additional assessments include body composition analysis, indirect calorimetry, and food and lifestyle diaries. The primary outcome will be changes in sleep quality from baseline. Secondary outcomes include anthropometric measurements, body composition, metabolic rate, biochemical and hormonal markers, inflammatory and oxidative stress markers, gut microbiota composition, and short-chain fatty acid production. The study has been approved by the Tuscany Regional Ethics Committee of the Azienda Ospedaliera Universitaria (AOU)—Careggi, Florence. Discussion This study will provide experimental data on how the timing of pasta consumption affects sleep quality and a range of health outcomes, contributing to the debate on the optimal timing of carbohydrate intake. Trial registration ClinicalTrials.gov NCT06185634. Registered on 07/01/2024.